PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI ( Studi di SATLANTAS POLRES Kediri ) - Joko Suparno (Universitas Islam Kadiri, 2019)
Leadership and organizational culture have an important role in improving employee performance. This study was conducted to examine how much influence the leadership style and organizational culture on employee performance. The purpose of this research is 1) To know the influence of leadership style on employee performance at Satlantas Polres Kediri; 2) To know the influence of leadership style on employee performance at Satlantas Polres Kediri; 3) To know the influence of leadership style and organizational culture simultaneously on employee performance at Satlantas Polres Kediri. This research uses quantitative approach. data collection was done through questionnaires distributed and executed on 68 employees at Satlantas Polres Kediri. Sampling to be used as respondent in this research is using purposive sampling method. The analysis used in this research is: multiple linear regression analysis, using research instrument test, classical assumption test, F test, and t test. The result of analysis shows that the leadership style (X1) variables are obtained coefficient of 0.339, t count 2.045 and significance value 0,045 which means if the leadership style variable 1 unit will improve the performance of employees at Satlantas Polres Kediri of 0.339 units. In other words the performance of employees will increase in line with the improvement of leadership style at Satlantas Polres Kediri. organizational culture variables (X2) obtained coefficient of 0.648, t-count 4,426 and significance value 0,000 which means if the organizational culture variable 1 unit will improve the performance of employees at Satlantas Polres Kediri of 0.648 units. In other words the performance of employees will increase in line with the improvement of organizational culture at Satlantas Polres Kediri. And the variables of leadership style (X1) and organizational culture (X2) were obtained F-count 38,595 and significance value 0,000 which means the variable of leadership style and organizational culture simultaneously influence the performance of the employees at Satlantas Polres Kediri.